Dehydrodipeptide hydrogelators containing naproxen N-capped tryptophan: self-assembly, hydrogel characterization, and evaluation as potential drug nanocarriers - Vilaça, Helena (2015)
In this work, we introduce dipeptides containing tryptophan N-capped with the nonsteroidal anti-inflammatory drug naproxen and C-terminal dehydroamino acids, dehydrophenylalanine (ΔPhe), dehydroaminobutyric acid (ΔAbu), and dehydroalanine (ΔAla) as efficacious protease resistant hydrogelators. Optimized conditions for gel formation are reported. Transmission electron microscopy experiments revealed that the hydrogels consist of networks of micro/nanosized fibers formed by peptide self-assembly. Fluorescence and circular dichroism spectroscopy indicate that the self-assembly process is driven by stacking interactions of the aromatic groups. The naphthalene groups of the naproxen moieties are highly organized in the fibers through chiral stacking. Rheological experiments demonstrated that the most hydrophobic peptide (containing C-terminal ΔPhe) formed more elastic gels at lower critical gelation concentrations. This gel revealed irreversible breakup, while the C-terminal ΔAbu and ΔAla gels, although less elastic, exhibited structural recovery and partial healing of the elastic properties. A potential antitumor thieno[3,2-b]pyridine derivative was incorporated (noncovalently) into the gel formed by the hydrogelator containing C-terminal ΔPhe residue. Fluorescence and Förster resonance energy transfer measurements indicate that the drug is located in a hydrophobic environment, near/associated with the peptide fibers, establishing this type of hydrogel as a good drug-nanocarrier candidate.